2017
DOI: 10.15288/jsad.2017.78.375
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption and Mortality From Coronary Heart Disease: An Updated Meta-Analysis of Cohort Studies

Abstract: Previous meta-analyses estimate that lowvolume alcohol consumption protects against coronary heart disease (CHD). Potential errors in studies include systematic misclassification of drinkers as abstainers, inadequate measurement, and selection bias across the life course. Method: Prospective studies of alcohol consumption and CHD mortality were identified in scholarly databases and reference lists. Studies were coded for potential abstainer biases and other study characteristics. The alcohol-CHD risk relations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
114
1
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 133 publications
(126 citation statements)
references
References 40 publications
(49 reference statements)
6
114
1
5
Order By: Relevance
“…The literature supports the fact that alcohol consumption, for the vast majority of conditions has a linear relationship between the volume of alcohol consumed and the risk of morbidity and mortality [15][16][17]. Alcohol abuse and dependence are clearly associated with an increased health service use and it has been shown that alcohol reduction and abstention in this specific population reduce health service use [8,18].…”
Section: Introductionmentioning
confidence: 67%
“…The literature supports the fact that alcohol consumption, for the vast majority of conditions has a linear relationship between the volume of alcohol consumed and the risk of morbidity and mortality [15][16][17]. Alcohol abuse and dependence are clearly associated with an increased health service use and it has been shown that alcohol reduction and abstention in this specific population reduce health service use [8,18].…”
Section: Introductionmentioning
confidence: 67%
“…However, our current meta‐analysis still lacks large‐scale or prospective studies on the relationship of ALDH2 gene G487A polymorphism and CAD. It is well known that the individuals without alcohol consumption have the higher CAD risk than the moderate drinkers . In the abstainers, the ALDH2 gene G487A polymorphism might not have the same role as that in the alcohol users.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in 2017, Zhao et al . also performed an updated meta‐analysis on the association of alcohol consumption and CAD mortality, they found that moderate alcohol use was associated with reduced CAD risk .…”
Section: Discussionmentioning
confidence: 99%
“…Вместе с тем употребление алкоголя, напротив, ассоциировалось с повышением летальности у лиц 55 лет и младше к моменту начала наблюдения. Для употреблявших спиртные напитки в прошлом ОР соста-вил 1,45, для эпизодически пьющих -1,44 [19].…”
Section: болезни сердечнососудистой системы и общая смертностьunclassified